Change in active microbial community structure, abundance and carbon cycling in an acid rice paddy soil with the addition of biochar. (17th November 2016) - Chen, J.; Sun, X.; Li, L.; Liu, X.; Zhang, B.; Zheng, J.; Pan, G.
Abstract : Biochar amendment of soil is known to enhance soil carbon sequestration and fertility. Its effect on soil microbial activity and functioning, however, is not well understood, particularly in field conditions. We collected topsoil samples from plots in a rice paddy in southwest China either amended with biochar for 18 months or not amended. Soil respiration, enzyme activity, total and metabolically active microbial community structures and abundances based on DNA and RNA, and functional diversity were determined. Soil organic carbon (SOC), total nitrogen (TN), pH and dissolved organic carbon (DOC) were significantly greater, and bulk density was less, under biochar amendment at 40 t ha −1 than for non‐amended soil. The addition of biochar generally reduced soil respiration, total and active fungal 18S gene abundances and β‐glucosidase activity, whereas it increased microbial biomass carbon and nitrogen, total and active bacterial 16S gene abundances, dehydrogenase and alkaline phosphatase activities. Furthermore, biochar amendment induced clear changes in the active microbial community structure and selected microorganisms with carbon substrates of polymers, and phenolic and amine compounds. Redundancy analysis indicated that the changes in soil pH and nutrient concentrations such as SOC, TN and DOC were of benefit mainly to the bacterial community rather than to the fungal one. Therefore, short‐term biochar amendment could help to slow down soil carbon turnover through increased efficiency of carbon use. In addition, soil microorganisms could potentially be selected to enable the use of some recalcitrant carbon substrates. Further investigations are needed to assess the underlying processes and potential effect of these changes on the mineralization of soil organic matter and ecosystem functioning in rice paddy soil. Highlights : Examined effect of biochar on soil microbial activity and its functioning 18 months after amendment. Biochar promoted total and metabolically active bacteria, but inhibited those of fungi over time. Biochar changed the active, but not the total community structures of bacteria and fungi. Biochar selected soil microorganisms with carbon substrates rich in aromatics.